2020
DOI: 10.3390/genes11070812
|View full text |Cite
|
Sign up to set email alerts
|

Preferentially Paternal Origin of De Novo 11p13 Chromosome Deletions Revealed in Patients with Congenital Aniridia and WAGR Syndrome

Abstract: The frequency of pathogenic large chromosome rearrangements detected in patients with different Mendelian diseases is truly diverse and can be remarkably high. Chromosome breaks could arise through different known mechanisms. Congenital PAX6-associated aniridia is a hereditary eye disorder caused by mutations or chromosome rearrangements involving the PAX6 gene. In our recent study, we identified 11p13 chromosome deletions in 30 out of 91 probands with congenital aniridia or WAGR syndrome (characterized by Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The frequency could be typical for the locus, as 11p13 deletions appeared to be characterized by some common features. Previously, we showed that the 11p13 locus had a propensity to be de novo broken, presumably on the paternal 11p13 chromosome [ 32 ]. Another peculiarity among the PAX6 gene features is a higher proportion between substitutions and small (<50 bp) indels, which was defined as 91:47 (approx.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency could be typical for the locus, as 11p13 deletions appeared to be characterized by some common features. Previously, we showed that the 11p13 locus had a propensity to be de novo broken, presumably on the paternal 11p13 chromosome [ 32 ]. Another peculiarity among the PAX6 gene features is a higher proportion between substitutions and small (<50 bp) indels, which was defined as 91:47 (approx.…”
Section: Discussionmentioning
confidence: 99%
“…Both single-and double-stranded breaks (SSB and DSB) are a common feature of cell karyotype studies after cannabis exposure [7][8][9][10]12,13,99]. It therefore becomes important in the present context to note that the epigenome plays an often determinative role in influencing or selecting the site of DNA breakage generally [118][119][120][121][122][123][124][125][126][127][128][129][130][131], during meiotic crossing over [132][133][134][135][136][137][138][139], in the immune gene hypervariable region [140][141][142][143][144][145][146], and in oncogenic pathways [120,123,124,[147][148][149][150][151][152][153]…”
Section: Epigenomic Impacts On Dna Breakage Sitesmentioning
confidence: 99%
“…This tumor almost invariably involves the development of an isochromosome 12p. Its presence is explained by the concept of presumptive pericentromeric chromatin dysregulation as the dysregulated pericentromeric epigenome presumably facilitates the aberrant scission of the chromosome at the centromere, forming the isochromosome through the interactions between the epigenome and the genome as described above [118][119][120][121][122][123][124][125][126][127][128][129][130][131]. The presence of KIT and KRAS (and to a lesser extent NRAS) on chromosome 12 then confers a growth advantage on the mutant clone, and malignant tumorigenesis is the end result of this process continued in the context of the gross re-sculpting of the chromosomal landscape by repeated cycles of the breakage-fusion-bridge cycle across multiple cell divisions that accumulate over time.…”
Section: Cannabinoids Deliver Multiple Carcinogenic Insultsmentioning
confidence: 99%